INTERGRATION BETWEEN MODERN LAWS WITH LIVING LAWS IN RURAL COMUNITIES IN THE RURAL ECONOMIC DEVELOPMENT - Kusumaputra, Ardhiwinda; Retnowati, Endang (TRUNOJOYO LAW REVIEW, 2019)
The purpose of this study is to find and analyze the integration between state modern laws and the living laws in the village, in its relation with national economic development and to find and analyze the ways to optimize national economic development through rural autonomy. The research method used is normative juridical, using legal material. The integration between state modern laws and the living law in the rural communities is by giving attention and accommodating the living laws in the rural communities especially in the economic order in the village including the establishment of Village-Owned Enterprises (BUMDes). In the formation of rules or laws relating to the economy or village empowerment, it should not only be juridical aspect that is prioritized but the philosophical, and sociological aspect of rural communities needs should be used as foundation . Reflection on the Pancasila understanding is also very necessary. This is because Pancasila is transformation result of various legal principles in Indonesia, Optimizing village economic development through rural autonomy by making improvements, and empowering all the potential of the village in particular the human resources and natural resources.